(untitled) (Scientific journal of the Fergana State University, 2025)
The water-physical properties of soils, the course of biological processes, the use of applied fertilizers, the growth, development and yield of cotton find the most favorable expression in those cases when the moisture content of the soil composition is within optimal limits.